PENDIDIKAN KARAKTER PADA ANAK USIA DINI - Dinda Afrillia Tanjung; Agustina Agustina; Putri Sania (EJoES (Educational Journal of Elementary School), 2020)
The character education is very important to build quality human resources. From an early age he was asked to have a commendable character as a result of good education. In this paper, we present character education theoretically in early childhood so that it has a basic foundation for early childhood character education. In addition, the role of parents and institutions also supports the success of this character education. This will create a generation that has a strong character.